2018
DOI: 10.3133/ofr20181017
|View full text |Cite
|
Sign up to set email alerts
|

Greater sage-grouse science (2015–17)—Synthesis and potential management implications

Abstract: For more information on the USGS-the Federal source for science about the Earth, its natural and living resources, natural hazards, and the environment-visit https://www.usgs.gov or call 1-888-ASK-USGS.For an overview of USGS information products, including maps, imagery, and publications, visit https://store.usgs.gov.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
(58 reference statements)
0
4
0
Order By: Relevance
“…The study uses 2015-18 survey observations to obtain survey and composited estimates of 13 land-health indicators of sagebrush communities in Wyoming Core and NonCore Greater Sage-Grouse (Centrocercus urophasianus) conservation areas [24][25][26] on BLM-managed lands. The Greater Sage-Grouse (hereafter sage-grouse) is a species of conservation concern in the western U.S. [27]. State-wide Core designations bound areas with large sage-grouse population sizes and have stringent stipulations limiting energy development and overall disturbance of sage-grouse populations and habitat [26].…”
Section: Plos Onementioning
confidence: 99%
“…The study uses 2015-18 survey observations to obtain survey and composited estimates of 13 land-health indicators of sagebrush communities in Wyoming Core and NonCore Greater Sage-Grouse (Centrocercus urophasianus) conservation areas [24][25][26] on BLM-managed lands. The Greater Sage-Grouse (hereafter sage-grouse) is a species of conservation concern in the western U.S. [27]. State-wide Core designations bound areas with large sage-grouse population sizes and have stringent stipulations limiting energy development and overall disturbance of sage-grouse populations and habitat [26].…”
Section: Plos Onementioning
confidence: 99%
“…Greater sage-grouse (Centrocercus urophasianus) embody this conflict. The wealth of research undertaken to inform a listing decision for the species (US DOI 2015) led BLM to request development of an online, searchable annotated bibliography (https://apps.usgs.gov/scien ce-for-re sou rce-managers) and science synthesis (Hanser et al 2018). Science syntheses in general are highly valued by managers (Seavy and Howell 2010), as are digital products that help managers easily find and access relevant science and aid in the comprehension of its core implications (Davis et al 2013).…”
Section: Data On the Presence And Condition Of Resources Of Concernmentioning
confidence: 99%
“…Finally, no new insights into the impacts of wild horses and burros, fence collision, recreation, or noise on Greater Sage-Grouse have been developed (Hanser et al 2018, p. 2).…”
Section: Diffuse Activitiesmentioning
confidence: 99%
“…Three studies of how grazing may affect Greater Sage-Grouse populations have been published since 2015 (Carter et al 2018;Hanser et al 2018). In Wyoming, Monroe et al (2017) found grazing effects depended on the timing and level of grazing.…”
Section: Impacts On Greater Sage-grousementioning
confidence: 99%